Aortic Root Distortion and Aortic Insufficiency During Balloon Angioplasty of the Right Ventricular Outflow Tract Prior to Transcatheter Pulmonary Valve Replacement. (29th January 2016) - Torres, Alejandro J.; McElhinney, Doff B.; Anderson, Brett R.; Turner, Mariel E.; Crystal, Matthew A.; Timchak, Donna M.; Vincent, Julie A.
Abstract : Objective: To describe the significance of aortic root distortion (AD) and/or aortic valve insufficiency (AI) during balloon angioplasty of the right ventricular outflow tract (RVOT) performed to rule out coronary artery compression prior to transcatheter pulmonary valve (TPV) implantation. Methods: AD/AI was assessed by retrospective review of all procedural aortographies performed to evaluate coronary anatomy prior to TPV implantation. AD/AI was also reviewed in all pre‐post MPV implant echocardiograms to assess for progression. Results: From 04/2007 to 3/2015, 118 pts underwent catheterization with intent for TPV implant. Mean age and weight were 24.5 ± 12 years and 64.3 ± 20 kg, respectively. Diagnoses were: TOF (53%), D‐TGA/DORV (18%), s/p Ross (15%), and Truncus (9%). Types of RV‐PA connections were: conduits (96), bioprosthetic valves (14), and other (7). Successful TPV implant occurred in 91 pts (77%). RVOT balloon angioplasty was performed in 43/118 pts (36%). Aortography was performed in 18/43 pts with AD/AI noted in 6/18 (33%); 2 with D‐TGA (1 s/p Lecompte, 1 s/p Rastelli), 2 with TOF, 1 Truncus and 1 s/p Ross. Procedure was aborted in the 2 who developed severe AD/AI. TPV was implanted in 3/4 patients with mild AD/AI. Review of pre‐post TPV implantation echocardiograms in 83/91 pts (91%) revealed no new/worsened AI in any patient. Conclusion: AD/AI is relatively common on aortography during simultaneous RVOT balloon angioplasty. Lack of AI progression by echocardiography post‐TPV implant suggests these may be benign findings in most cases. However, AD/AI should be carefully evaluated in certain anatomic subtypes with close RVOT/aortic alignments. (J Interven Cardiol 2016;29:197–207)